Employment as a Part of Rehabilitation: A Review of Similarities and Differences between Female and Male Criminals - Joanna Felczak (Studia Iuridica Lublinensia, 2023)
In this review article, the latest knowledge in the area of the importance of employment in the process of rehabilitation is presented. The goal is a literature review and an analysis of the similarities and differences between female and male criminals in the context of employment during the prison sentence and the chances of finding employment after release. Also, the relationships between employment and later recidivism are analyzed. To present the relationship between employment and recidivism holistically, the following points were referred to: the role of work in rehabilitation and adaptation to freedom; differences between males and females in employment experiences and peculiarities in social background affecting their labour force attachment; the employment of prisoners before, during and after punishment; opportunities and barriers in finding a job by former prisoners; bidirectional relationship – employment as a way to reintegrate ex-offender with the society and as a way to prevent recidivism. Different phases of rehabilitation (being in prison, leaving prison) were distinguished and labour force attachment prior to imprisonment spell were also discussed. Also, the article consists of a discussion section where conclusions and recommendations are presented. The indications for further research were also listed, one of which is to examine the real benefit of the work of convicts – whether it provides the possibility of subsistence. In the article, study results from various countries, and consequently, various judicial systems, are referred to.